Comparative genomics and phenotypes of Listeria monocytogenes isolated from enoki mushrooms in South Korea and China - Wen Si Hu; So Hyeon An; Dong Woo Kim; Hyeong Uk Im; Seung Hun Lee; Yu Bao Li; Zi Xuan Liu; Zhi Wei Wang; A Ram Lee; Ui In Kim; Hyeon Ji Je; Yeon Ju Seo; et al. (Food Microbiology, 2026)

Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Interaction of SFPQ with S100A8 and S100A9 in EoL-1 and EoL-1-IR cells - Jae Ha Baek; Geunyeong Kim; Yujin Hong; Min Hwa Hong; Ji-Sook Lee; Ik-Chan Song; Soo-Jung Gong; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Establishing a gravity observation system using a superconducting gravimeter: toward future applications - Gracia Kim; In-Mook Choi; Hong Jong Oh; Danbi Hong (Geosciences Journal, 2026)

Reducing greenhouse gas emissions while improving rice yield and water use efficiency in rice paddies through mid-season drainage and intermittent irrigation - Su-Heon Jang; Jae-In Lee; Chang-Gu Lee; Gil Won Kim; Jin-Kyung Hong; Seong-Jik Park (Agriculture, Ecosystems & Environment, 2026)

Evaluation of the Korean Weathex WxR-301D Radiosonde Against the Vaisala RS41: Temperature Consistency and Humidity Performance in Moist Environments - Byeongtaek Kim; Sungeun Hwang; Sora In; Youngtae Lee; Reno Choi; Jaewon Kim; Seonok Hong; Jaewon So; Kihoon Kim (Asia-Pacific Journal of Atmospheric Sciences, 2026)
Radiosondes are essential for atmospheric profiling, offering high-resolution observations of thermodynamic and kinematic parameters. This presents a comparative assessment of the Vaisala RS41 and the Weathex (Korean company) WxR-301D radiosondes based on 46 dual soundings conducted during a summer field campaign over Jeju Island, South Korea. Simultaneous temperature and relative humidity measurements were analyzed under diverse synoptic conditions, including clear, cloudy, foggy, and rainy cases. The RS41 and WxR-301D exhibited strong agreement in temperature measurements, with a mean absolute error of 1.19 °C across altitude and diurnal cycles. However, humidity observations revealed systematic differences: the WxR-301D exhibited increased variability and a tendency to overestimate humidity under rainy conditions, particularly in the upper troposphere and lower stratosphere. An ISSR-based case analysis further revealed pronounced discrepancies in humidity profiles between the two radiosondes. While the RS41 indicated a realistic drying trend within and above the ISSR, the WxR-301D maintained elevated humidity values exceeding 60% in the stratosphere, suggesting possible sensor wetting or icing effects, or measurement lag. These results highlight the importance of evaluating the performance of unheated humidity sensors under cold and moist atmospheric conditions. The results provide a basis for refining operational radiosonde quality control and sensor calibration protocols.

Childhood exposure to traffic-related air pollution and lung function at age 10 years: evidence of nutritional modification in a birth cohort - Yujin Park; Dong-Wook Lee; Choong Ho Shin; Young Ah Lee; Yun Jeong Lee; Dong In Suh; Yun-Chul Hong; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Soontae Kim; Kyoung-Nam Kim (International Journal of Hygiene and Environmental Health, 2026)

Bioactive fibrous microwell platforms induce m1 macrophage clusters that enhance anti-tumor activity and T cell polarization - Juhwan Choi; Yongpyo Hong; Chungmo Heo; Eunji Yeom; Taehyeon Kim; In Seok Moon; Won-Gun Koh (Chemical Engineering Journal, 2026)

Episodic and source-resolved VOC emissions in a petrochemical complex: Insights from real-time measurements - Se-In Hong; Soyoung Park; Jaewook Kim; Sungjin Park; Jihye Moon; Joost de Gouw; Jungho Yu; Seonjin Yoon; Jeungwoon Kim; Hwajin Kim (Environmental Pollution, 2026)

Ubiquilin 1 Inhibits intracellular proliferation of Salmonella enterica serovar Typhimurium through Xenophagy - In Sook Jeon; Yong-Hee Lee; Jin Tae Hong; Won Seop Kim; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2026)

Role of CRM1-mediated SFPQ/S100A8 complex formation in psoriasis - Geunyeong Kim; Yujin Hong; Ji-Sook Lee; Juram Lee; Tae Young Han; In Sik Kim (Molecular & Cellular Toxicology, 2026)

Unveiling uncertainty in microplastic quantification: Artificial intelligence integrated Raman analysis - Min Young Oh; In-Chun Jeong; Kihyun Kim; Jeein Hong; Minseon Ju; Jaebum Choo; Ji-Hyun Kim; Sungguan Hong (Journal of Hazardous Materials, 2026)

Dyella stictolepturae sp. nov., isolated from the larva gut of red-brown longhorn beetle (Stictoleptura succedanea) - Bora Kim; Ah-In Yang; Sung-Hong Joe; Hae-In Joe; Na-Ri Shin (Antonie van Leeuwenhoek, 2026)

RNAseq-based molecular insights into three insecticide resistances in Laodelphax striatellus: Structural perspective on CYP6ER2 in detoxification - Minyoung Choi; Murtaza Khan; In-hong Jeong; Juil Kim (Pesticide Biochemistry and Physiology, 2026)

Nuclear receptor ERR contributes to imidacloprid resistance by upregulating cytochrome P450 in Nilaparvata lugens - Woo-Ram Park; Byungyoon Choi; Nanthini Sadasivam; Hui-Jin Bae; Sunmin Kim; Eunae Kim; Hueng-Sik Choi; In-Hong Jeong; Don-Kyu Kim (Insect Biochemistry and Molecular Biology, 2026)

Antrihabitans auranticaus sp. nov., Isolated from a Cave, and Emended Description of the Genus Antrihabitans - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Current Microbiology, 2026)

Current contamination trends and historical records of traditional and emerging polycyclic aromatic hydrocarbons in sediments from Yeongil Bay and Hupo Region, East Sea - Jihyun Cha; Chang-Eon Lee; Mungi Kim; Youngnam Kim; Jiyun Gwak; Dong Jin Joe; Jae-Hyun Lim; In Kwon Um; Man Sik Choi; Seongjin Hong (Marine Pollution Bulletin, 2026)

Serine protease–viscoelastic polysaccharide interaction in inorganic CaCO3: Enhanced thermal stability for efficient enzyme particulation via immobilization - Soyoon Baek; Chan Hee Lee; Dain Kim; Jinhee Jeong; In Ki Hong; Seunghee Bae; Ee Taek Hwang (Carbohydrate Polymers, 2025)

Microbacterium insectihabitans sp. nov., Isolated from Larvae of Allomyrina dichotoma - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Current Microbiology, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

Actinomadura opuntiae Sp. Nov., Isolated from a Soil of Cactus and the Reclassification of Actinomadura namibiensis Wink Et Al. 2003 as a Later Heterotypic Synonym of Actinomadura kijaniata Horan and Brodsky 1982 - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Current Microbiology, 2025)

Collagenase and tyrosinase inhibitory compounds from fish gut bacteria Ruegeria atlantica and Pseudoalteromonas neustonica - Jonghwan Kim; Su Jung Hwang; Gyu Sung Lee; Ju Ryeong Lee; Hye In An; Hong Sik Im; Minji Kim; Sang-Seob Lee; Hyo-Jong Lee; Chung Sub Kim (Phytochemistry Letters, 2025)

Development of a feedback-regulated temperature control system to enable supercooling reversion in beef preservation - Seokhyeon Yun; Taeho Kim; In-U Jeong; Song-Yi Choi; Soyeon Kim; Jin Hong Mok; Taiyoung Kang (Innovative Food Science & Emerging Technologies, 2025)

Improving acid-free and selective leaching of lithium from end-of-life LiFePO4 batteries using sodium persulfate: Impact of removing organic matter by thermal treatment in an inert atmosphere - Jong-Won Choi; Mooki Bae; Hyunju Lee; Hong-In Kim; Hyun-Woo Shim; Jinyoung Je; Gigap Han; Junhyun Choi; Hyunjoon Lee; Sookyung Kim (Hydrometallurgy, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Preclinical Pharmacokinetics of DM5167, a Novel Selective PARP1 Inhibitor - Jin Woo Kim; Seung-Won Lee; Myung Eun Jung; Ki-Hong Jang; Hae-In Choi; Yoon Ha Lee; Jeongmin Kim; Sunjoo Ahn; Eunhee Kim; Tae-Sung Koo (Pharmaceutical Research, 2025)

Microbacterium xanthum sp. nov. Isolated from Seaweed, with the Reclassification of Microbacterium ihumii Yacouba et al. 2023 as a Later Heterotypic Synonym of Microbacterium tenebrionis Lee and Kim 2023 - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Current Microbiology, 2025)

AI-driven multivariate time series forecasting of transmembrane pressure in ultrafiltration: A stationarity-aware approach - Dongju Kim; Jong Pil Yun; Taehan Lee; Daewoong Jung; Hong-In Won (Journal of Water Process Engineering, 2025)

Effect of mealworm component and extrusion temperature on fibrous structure formation and physicochemical properties of meat analog extrudates - Chhychhy Chao; Jang Hong Lee; Hyun Woo Kim; In Woo Kim; Hyun Jin Park; Su Hyun Lee (Food Chemistry, 2025)

A Dual-Modality nanozyme Exploiting ROS-Responsive oxygen Catalysis for Precision NF-κB pathway Suppression in gouty arthritis - Sathiyamoorthy Padmanaban; Sree Samanvitha Kuppa; Omkar Sangabathula; Amal Babu; Adityanarayan Mohapatra; Sung Sun Kim; Hong Yeol Yang; Aravindkumar Sundaram; Hyung Keun Kim; Jong Keun Seon; In-Kyu Park (Chemical Engineering Journal, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

RNA-seq-based identification of imidacloprid resistance mechanisms in Nilaparvata lugens and development of diagnostic tools for the CYP6ER1 variant - Minyoung Choi; Murtaza Khan; Changhee Han; In-hong Jeong; Nakjung Choi; Juil Kim (Pesticide Biochemistry and Physiology, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Genetic parameters for whole weight and survival rate of the Portuguese oyster, Crassostrea angulata, at different harvest stages after six generations of selection - In Van Vu; Pierre Boudry; Thiyagarajan Vengatesen; Almas Gheyas; Tran Dang Khanh; Thi Mai Nguyen; Hsu Htoo; Hyun Woo Kim; Shantanu Kundu; Tran Thi Nguyet Minh; Do Thi Thanh Trung; Thu Thi Anh Nguyen; et al. (Aquaculture International, 2025)

Applicability of plant–clay mineral composite for rapid algae removal from eutrophic freshwaters at the laboratory and field scales - Byeong-Hun Han; Hyo Gyeom Kim; Young-Hyo Kim; In-Hwan Cho; Ha-Kyung Kim; Sungwon Hong; Baik-Ho Kim (Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Direct aluminate precipitation technique with a phase transformation strategy for selective lithium extraction from Uyuni brine - Hee Seo Kim; Yong Jae Suh; Dae-Woo Kim; Heeji Yoo; Hye-Jin Hong; In-Su Park (Chemical Engineering Journal, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Evaluation of different fat sources and their combinations on growth performance, nutrient digestibility, fecal score, and meat quality of pigs of different ages - Md Raihanul Hoque; Jae Hong Park; In Ho Kim (Animal Feed Science and Technology, 2025)

Tribuli Fructus alleviates 1-methyl-4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinson’s disease by suppressing neuroinflammation via JNK signaling - Jin Hee Kim; Eugene Huh; Hyeyoon Eo; Jin Se Kim; Youngji Kwon; In Gyoung Ju; Yujin Choi; Hae-Jee Yoon; So-Ri Son; Dae Sik Jang; Seon-Pyo Hong; Hi-Joon Park; et al. (Metabolic Brain Disease, 2024)

Preparation of fragmented polyethylene nanoplastics using a focused ultrasonic system and assessment of their cytotoxic effects on human cells - Seonae Hwangbo; In Young Kim; Kwanyoung Ko; Kyungtae Park; Jinkee Hong; Gwansuk Kang; Jung-Sub Wi; Jaeseok Kim; Tae Geol Lee (Environmental Pollution, 2024)

Distribution coefficient prediction using multimodal machine learning based on soil adsorption factors, XRF, and XRD spectrum data - Seongyeon Na; Heewon Jeong; Ilgook Kim; Seok Min Hong; Jaegyu Shim; In-Ho Yoon; Kyung Hwa Cho (Journal of Hazardous Materials, 2024)

Olaparib synergically exacerbates the radiation-induced intestinal apoptosis in mice - Sohee Jeong; Jeongmin Lee; Jun Hong Park; Yeonghoon Son; Hae-June Lee; Changjong Moon; In Sik Shin; Joong Sun Kim; Sohi Kang (Molecular & Cellular Toxicology, 2024)

Understanding the Impact of SARS-CoV-2 on Lung Endothelial Cells: Brief Mechanisms Unveiled - Fahad Hassan Shah; Jun Young Bang; Yoon Seok Nam; In Seo Hwang; Dae Hong Kim; Minkyoung Ki; Saad Salman; Heon-Woo Lee (Cell Biochemistry and Biophysics, 2024)

Consumer-driven characterization of healing foods using Q methodology and Q based sorting - Ki-Beom Song; Sébastien Lê; Haeng-Ran Kim; Seon-Mi Yoo; Min-Sook Kang; Han-Na Chu; In-Seon Hwang; Jae-Hee Hong (Food Quality and Preference, 2024)

Ether vs. Carbonate solvents in Na–CuS Batteries: Impact on anode Morphology, SEI Formation, and desolvation dynamics - Young-Hoon Kim; Son-Jae Sim; Yeong-In Yoon; Yong-Seok Choi; Hong-Kyu Kim; Jae-Chul Lee (Chemical Engineering Journal, 2024)

Pharmacokinetics and extensive intestinal first-pass effects of apigenin and its active metabolite, apigenin-7-O-glucuronide, in rats - Seong-Wook Seo; Soon Ho Choi; Jung-Ki Hong; Kyoung Mi Kim; Se Chan Kang; In-Soo Yoon (Journal of Pharmaceutical Investigation, 2024)

Feasibility study of Aesculus turbinata fruit shell-derived biochar for ammonia removal in wastewater and its subsequent use as nitrogen fertilizer - Jae-In Lee; Chuluuntsetseg Jadamba; Chang-Gu Lee; Sung-Chang Hong; Jin-Ho Kim; Soo-Cheul Yoo; Seong-Jik Park (Chemosphere, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Correction to: Microbacterium aquilitoris sp. nov. and Microbacterium gawkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yan; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Efficient full-color daytime radiative cooling with diffuse-reflection-dominant cholesteric liquid crystals - Sangwok Bae; Minjeong Kim; Gumin Kang; Hong-Sub Lee; In Soo Kim; Suk-Won Choi; Jin Gu Kang (Chemical Engineering Journal, 2024)

Protective effect of Luffa cylindrica Roemer against dexamethasone-induced muscle atrophy in primary rat skeletal muscle cells - Changhwan Yeo; Hyunseong Kim; Wan-Jin Jeon; Junseon Lee; Jin Young Hong; Hyun Kim; Yoon Jae Lee; Seung Ho Baek; In-Hyuk Ha (Journal of Muscle Research and Cell Motility, 2024)
Glucocorticoids (GCs) are commonly used in the treatment of chronic inflammatory conditions. However, the administration of high doses and long-term use of GCs can induce muscle atrophy (MA) in patients, leading to a decline in quality of life and increased mortality. MA leads to protein degradation in skeletal muscle, resulting in a reduction of muscle mass. This process is triggered by GCs like dexamethasone (DEX), which induce the expression of E3 ubiquitin ligases, namely Atrogin-1 and muscle RING-finger protein-1 (MuRF1). In this study, we examined the anti-MA potential of Luffa cylindrica Roemer (LCR) on DEX-treated primary skeletal myotubes. Primary skeletal myotubes stimulated with LCR alone resulted in a significant upregulation of myotube development, characterized by an increase in both the number and diameter of myotubes. Contrastingly, combined treatment with LCR and DEX reduced the expression of Atrogin-1, while treatment with DEX alone induced the expression of MuRF1. Furthermore, LCR treatment successfully restored the number and diameter of myotubes that had been diminished by DEX treatment. These findings suggest that LCR holds potential for treating MA, as an accelerating effect on muscle development and anti-MA effects on primary skeletal muscle cells were observed.

Microbacterium aquilitoris sp. nov. and Microbacterium gwkjiense sp. nov., isolated from beach - Soon Dong Lee; Hong Lim Yang; Ji-Sun Kim; In Seop Kim (Archives of Microbiology, 2024)

Corrigendum to “Status, supply chain, challenges, and opportunities to advance oyster aquaculture in northern Vietnam” [Aquaculture Volume 572, July 2023] - Sarah C. Ugalde; Sang V. Vu; Cao Truong Giang; Nguyen Thi Hong Ngoc; Thi Kim Anh Tran; John D. Mullen; Vu Van In; Wayne O'Connor (Aquaculture, 2024)

Submarine landslides on the Eastern South Korea Plateau (ESKP)—Do pumice-rich tephra layers control slope stability? - Deniz Cukur; In-Kwon Um; David M. Buchs; Seong-Pil Kim; Gee-Soo Kong; Jong-Hwa Chun; Senay Horozal; Seok-Hwi Hong; Shin Yu; Tae-Yeon Kim (Marine Geology, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

Electron donor–acceptor type delayed fluorescence emitters with inverted singlet and triplet excited states - Youngnam Lee; Jiyun Kim; Soohyeon Lee; Eunji Sim; Jong-In Hong (Chemical Engineering Journal, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Led-mediated instantaneous pore formation in membranes driven by structural transformation and deprotonation of phospholipids - Hui Bang Cho; Hye Jin Kim; Hye-Ryoung Kim; Sujeong Lee; Ji-In Park; Keun-Hong Park (Chemical Engineering Journal, 2023)

Neuregulin-1 suppresses anti-apoptotic effect of Der p 38 on neutrophils by inhibition of cytokine secretion - Yujin Hong; Ji Hyeon Choi; Min Hwa Hong; Geunyeong Kim; Ji-Sook Lee; Ran-Sook Woo; Eun Ju Yang; In Sik Kim (Molecular & Cellular Toxicology, 2023)

Vulnerability assessment of Korean fisheries to climate change - Moo-Jin Kim; Jae-Beum Hong; In-Seong Han; Joon-Soo Lee; Do-Hoon Kim (Marine Policy, 2023)

Adsorptive recovery of rare earth elements from aqueous solution by citric acid crosslinked carboxymethylated cellulose nanofibril aerogel - Hee Seo Kim; Dae-Woo Kim; In-Su Park; Hye-Jin Hong (Journal of Cleaner Production, 2023)

Defect-enriched red phosphorus nanosheets as efficient and stable photothermal absorber material for interfacial solar desalination - Tatachari Santhanagopalan Shridharan; Arumugam Sivanantham; Runfa Tan; Seo Yeong Hong; Dong Hoe Kim; In Sun Cho (Desalination, 2023)

Disruption of type I interferon pathway and reduced production of IFN-α by parabens in virus-infected dendritic cells - In-Gu Lee; Yong-Hyun Joo; Hoyeon Jeon; Jung-Woong Kim; Young-Jin Seo; So-Hee Hong (Genes & Genomics, 2023)

Investigation of 3D-printable chickpea-mealworm protein mixtures and their bolus rheology: A soft-textured and safe-swallowing food for the elderly - Chhychhy Chao; Jang Hong Lee; In Woo Kim; Ra Yeong Choi; Hyun Woo Kim; Hyun Jin Park (Food Bioscience, 2023)

Evaluation of fermented soybean meal and edible insect hydrolysates as potential serum replacement in pig muscle stem cell culture - Cho Hyun Kim; Hyun Jung Lee; Doo Yeon Jung; Minsu Kim; Hyun Young Jung; Heesang Hong; Yun-Sang Choi; Hae In Yong; Cheorun Jo (Food Bioscience, 2023)

Status, supply chain, challenges, and opportunities to advance oyster aquaculture in northern Vietnam - Sarah C. Ugalde; Sang V. Vu; Cao Truong Giang; Nguyen Thi Hong Ngoc; Thi Kim Anh Tran; John D. Mullen; Vu Van In; Wayne O'Connor (Aquaculture, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Clean power generation from salinity gradient using reverse electrodialysis technologies: Recent advances, bottlenecks, and future direction - Soryong Chae; Hanki Kim; Jin Gi Hong; Jaewon Jang; Mitsuru Higa; Mohammad Pishnamazi; Ji-Yeon Choi; Ramali Chandula Walgama; Chulsung Bae; In S. Kim; Jin-Soo Park (Chemical Engineering Journal, 2023)

Display of Streptococcus iniae α-Enolase on the Surface of Virus-Like Particles (VLPs) of Nervous Necrosis Virus (NNV) Using SpyTag/SpyCatcher - Jeong In Yang; Ki Hong Kim (Marine Biotechnology, 2022)

Performance evaluation of a visual guidance patient-controlled respiratory gating system for respiratory-gated magnetic-resonance image-guided radiation therapy - Hyung Jin Choun; Jung-in Kim; Chang Heon Choi; Seongmoon Jung; Hyeongmin Jin; Hong-Gyun Wu; Eui Kyu Chie; Jong Min Park (Physical and Engineering Sciences in Medicine, 2022)

Oculomics for sarcopenia prediction: a machine learning approach toward predictive, preventive, and personalized medicine - Bo Ram Kim; Tae Keun Yoo; Hong Kyu Kim; Ik Hee Ryu; Jin Kuk Kim; In Sik Lee; Jung Soo Kim; Dong-Hyeok Shin; Young-Sang Kim; Bom Taeck Kim (EPMA Journal, 2022)

The Neuropeptide Spexin Promotes the Osteoblast Differentiation of MC3T3-E1 Cells via the MEK/ERK Pathway and Bone Regeneration in a Mouse Calvarial Defect Model - Freshet Assefa; Ju Ang Kim; Jiwon Lim; Sang-Hyeon Nam; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2022)

Tissue-specific DNA damage response in Mouse Whole-body irradiation - Seon-Gyeong Lee; Namwoo Kim; In Bae Park; Jun Hong Park; Kyungjae Myung (Molecular & Cellular Toxicology, 2022)
Background Genomic instability is a hallmark of various cancers, and DNA repair is an essential process for maintaining genomic integrity. Mammalian cells have developed various DNA repair mechanisms in response to DNA damage. Compared to the cellular response to DNA damage, the in vivo DNA damage response (DDR) of specific tissues has not been studied extensively. Objective In this study, mice were exposed to whole-body gamma (γ)-irradiation to evaluate the specific DDR of various tissues. We treated male C57BL6/J mice with γ-irradiation at different doses, and the DDR protein levels in different tissues were analyzed. Results The level of gamma-H2A histone family member X (γH2AX) increased in most organs after exposure to γ-irradiation. In particular, the liver, lung, and kidney tissues showed higher γH2AX induction upon DNA damage, compared to that in the brain, muscle, and testis tissues. RAD51 was highly expressed in the testis, irrespective of irradiation. The levels of proliferating cell nuclear antigen (PCNA) and ubiquitinated PCNA increased in lung tissues upon irradiation, suggesting that the post-replication repair may mainly operate in the lungs in response to γ-irradiation. Conclusion These results suggest that each tissue has a preferable repair mechanism in response to γ-irradiation. Therefore, the understanding and application of tissue-specific DNA damage responses could improve the clinical approach of radiotherapy for treating specific cancers.

Correction to: Rouxiella aceris sp. nov., isolated from tree sap and the emended description of the genus Rouxiella - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Antonie van Leeuwenhoek, 2021)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

Assessment of the abuse potential of methamnetamine in rodents: a behavioral pharmacology study - Dong-Hyun Youn; Jin Mook Kim; Young-ki Hong; Seo-In Park; Jin-Moo Lee; Young-Hoon Kim; Chang Won Park; Mi Sun Kang (Psychopharmacology, 2021)

Rouxiella aceris sp. nov., isolated from tree sap and the emended description of the genus Rouxiella - Soon Dong Lee; Hong Lim Yang; In Seop Kim (Antonie van Leeuwenhoek, 2021)

Ambient temperature regulates uncoupling protein 1 expression but fails to induce adipocyte browning in zebrafish - Yousheng Mao; KwangHeum Hong; Sushil Bhandari; Li Li; Weifang Liao; SeongJin Kim; Yinyi Xiong; In-Koo Nam; Seong-Kyu Choe; SeongAe Kwak (Advances in Traditional Medicine, 2021)

Source identification and assessment of heavy metal contamination in urban soils based on cluster analysis and multiple pollution indices - Hong-gil Lee; Hyun-Koo Kim; Hoe-Jung Noh; Yoon Joo Byun; Hyen-Mi Chung; Ji-In Kim (Journal of Soils and Sediments, 2021)

Hongsoonwoonella zoysiae gen. nov., sp. nov., a new member of the family Stappiaceae isolated from a tidal mudflat - Soon Dong Lee; Sung-Min Kim; Hong Lim Yang; Yeong-Sik Byeon; In Seop Kim (Archives of Microbiology, 2021)

Transglutaminase 2 mediates transcriptional regulation through BAF250a polyamination - Hyo-Jun Kim; Jin-Haeng Lee; Sung-Yup Cho; Ju-Hong Jeon; In-Gyu Kim (Genes & Genomics, 2021)

A novel apoptosis probe, cyclic ApoPep-1, for in vivo imaging with multimodal applications in chronic inflammatory arthritis - In-Seop So; Jin Hee Kang; Jung Wan Hong; Shijin Sung; Al Faruque Hasan; Keum Hee Sa; Seung Woo Han; In San Kim; Young Mo Kang (Apoptosis, 2021)

Effect of different planting times on the quantitative variation of total seed isoflavone content and composition in Korean soybean cultivars (Glycine max (L.) Merr.) - Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Tae-Joung Ha; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
There is great interest in the enhancement of isoflavones as one of the functional ingredients in soybean. This study aimed to investigate the effects of changes in the ecological environment over different planting times on isoflavone content. A total of 28 Korean soybean cultivars were grown at different planting times in late May, mid-June, and early July and their isoflavone content was measured over 2 years (2017 and 2018). Analyses of variance revealed significant effects of genotypes, planting times, years, and their interactions on isoflavone content. The average content of total isoflavone, as well as its component groups of malonylglucoside and aglycon, increased significantly as the seed planting time was delayed from late May to early July. The accumulation of each isoflavone component varied with changes in the planting time. The isoflavone content of the soybean cultivars for soy-sprout and soy-paste and tofu were higher for plantings in early July than for those in late May and/or mid-June, except for the black soybean cultivars. Despite significant correlations of the isoflavone content of the 28 cultivars among the three planting times, the responses of individual cultivars varied in isoflavone content by planting time. When planting was delayed, the time to flowering and maturity was also delayed and the number of days of growth from planting or flowering to maturity decreased; however, this was not related to isoflavone content. When planting was delayed, the temperature during the ripening period from flowering to maturity was lower, which was inversely related to the isoflavone content.

Corneal Repair with Adhesive Cell Sheets of Fetal Cartilage-Derived Stem Cells - In-Su Park; Byeong Kook Kim; Minh-Dung Truong; Hong Seok Yang; Sang-Hyug Park; Hyo Soon Park; Byung Hyune Choi; Bae Hie Won; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2021)

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

N-type Cav channel inhibition by spider venom peptide of Argiope bruennichi - In-Wook Hwang; Min Kyoung Shin; Yoo-Jung Lee; Seung Tae Kim; Sue Yeon Lee; Byungjo Lee; Wonhee Jang; Joo-Hong Yeo; Seungki Lee; Jung-Suk Sung (Molecular & Cellular Toxicology, 2021)

Analysis of differentially expressed genes in soybean leaf tissue of tolerant and susceptible cultivars under flooding stress revealed by RNA sequencing - Sanjeev K. Dhungana; Hong-Sik Kim; Beom-Kyu Kang; Jeong-Hyun Seo; Hyun-Tae Kim; Jae-Hyeon Oh; Sang-Ouk Shin; In-Yeol Baek (Journal of Crop Science and Biotechnology, 2021)
Flooding stress causes severe yield reduction in soybean worldwide. The development of stress-tolerant cultivars could be an effective measure to reduce the negative effects of flooding stress. Molecular information on the gene expression pattern of tolerant and susceptible genotypes under flooding stress could be valuable to improve the flooding tolerance in soybean. The objective of this study was to analyze the differentially expressed genes (DEGs) revealed by RNA sequencing in the soybean leaf tissues of tolerant (‘Paldalkong’ and ‘Danbaekkong’) and susceptible (‘NTS1116’) cultivars under flooding stress. Seedlings were grown in a well-watered condition up to the V1–V2 stage and flood-stressed by inundating ~ 10-cm water for 14 days. A total of 22,468 genes were differentially expressed in flood-stressed condition compared to the well-watered control condition, out of which 13,729, 13,405, and 13,160 were differentially expressed in ‘Paldalkong’, ‘Danbaekkong’, and ‘NTS1116’, respectively. A higher number of some of the flooding tolerance-related genes such as lipoxygenase, expansin, glutathione S-transferase, and sugar efflux transporter were up-regulated in the tolerant cultivars than in the susceptible cultivar. The number of some abscisic acid-related transcription factors of basic leucine zipper domain and myeloblastosis families was also higher in the tolerant cultivars than in the susceptible cultivar. The molecular information about the DEGs of tolerant and susceptible cultivars obtained in the present study could be valuable to improve the flooding tolerance in soybeans.

Biological activities and chemical components of Potentilla kleiniana Wight & Arn - Song Hua Xuan; In Ki Hong; Yun Ju Lee; Ji Woong Kim; Soo Nam Park (Natural Product Research, 2020)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

Recent changes in heatwave characteristics over Korea - Donghyuck Yoon; Dong-Hyun Cha; Myong-In Lee; Ki-Hong Min; Joowan Kim; Sang-Yoon Jun; Yonghan Choi (Climate Dynamics, 2020)

High-throughput phenotyping platform for analyzing drought tolerance in rice - Song Lim Kim; Nyunhee Kim; Hongseok Lee; Eungyeong Lee; Kyeong-Seong Cheon; Minsu Kim; JeongHo Baek; Inchan Choi; Hyeonso Ji; In Sun Yoon; Ki-Hong Jung; Taek-Ryoun Kwon; et al. (Planta, 2020)
Main conclusion A new imaging platform was constructed to analyze drought-tolerant traits of rice. Rice was used to quantify drought phenotypes through image-based parameters and analyzing tools. Abstract Climate change has increased the frequency and severity of drought, which limits crop production worldwide. Developing new cultivars with increased drought tolerance and short breeding cycles is critical. However, achieving this goal requires phenotyping a large number of breeding populations in a short time and in an accurate manner. Novel cutting-edge technologies such as those based on remote sensors are being applied to solve this problem. In this study, new technologies were applied to obtain and analyze imaging data and establish efficient screening platforms for drought tolerance in rice using the drought-tolerant mutant osphyb . Red–Green–Blue images were used to predict plant area, color, and compactness. Near-infrared imaging was used to determine the water content of rice, infrared was used to assess plant temperature, and fluorescence was used to examine photosynthesis efficiency. DroughtSpotter technology was used to determine water use efficiency, plant water loss rate, and transpiration rate. The results indicate that these methods can detect the difference between tolerant and susceptible plants, suggesting their value as high-throughput phenotyping methods for short breeding cycles as well as for functional genetic studies of tolerance to drought stress.

De novo assembly and characterization of transcriptome in the medicinal plant Euphorbia jolkini - Neha Samir Roy; In-hye Lee; Jung-A Kim; Rahul Vasudeo Ramekar; Kyong-Cheul Park; Nam-il Park; Joo-Hong Yeo; Ik-Young Choi; Soonok Kim (Genes & Genomics, 2020)

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Microsatellite records for volume 12, issue 2 - In-Chul Bang; Fleur Bruggemann; Chen Chen; Quentin D’Alexis; Hongmei Gao; Pauline Gélin; Xiaoyou Hong; Miho Inoue-Murayama; Kang-Rae Kim; Yeong-Ho Kwak; Wei Li; Haitao Ma; et al. (Conservation Genetics Resources, 2020)

Development of powdery mildew race 5-specific SNP markers in Cucumis melo L. using whole-genome resequencing - Jewel Howlader; Yeji Hong; Sathishkumar Natarajan; Kanij Rukshana Sumi; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Genome-wide analysis of spatiotemporal gene expression patterns during floral organ development in Brassica rapa - Soo In Lee; Muthusamy Muthusamy; Muhammad Amjad Nawaz; Joon Ki Hong; Myung-Ho Lim; Jin A. Kim; Mi-Jeong Jeong (Molecular Genetics and Genomics, 2019)

Metagenomic analysis of relationships between the denitrification process and carbon metabolism in a bioaugmented full-scale tannery wastewater treatment plant - S. Aalfin Emmanuel; Woo Jun Sul; Hoon Je Seong; Chaeyoung Rhee; Kalu I. Ekpheghere; In-Soo Kim; Hong-Gi Kim; Sung-Cheol Koh (World Journal of Microbiology and Biotechnology, 2019)

Reversine induces caspase-dependent apoptosis of human osteosarcoma cells through extrinsic and intrinsic apoptotic signaling pathways - Jae-Sung Kim; In-A Cho; Kyeong-Rok Kang; HyangI Lim; Tae-Hyeon Kim; Sun-Kyoung Yu; Heung-Joong Kim; Seul Ah Lee; Sung Min Moon; Hong Sung Chun; Chun Sung Kim; Do Kyung Kim (Genes & Genomics, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Severe Cardiomyopathy Due to Arthroprosthetic Cobaltism: Report of Two Cases with Different Outcomes - Hyo-In Choi; Jung Ae Hong; Min-Seok Kim; Sang Eun Lee; Sung-Ho Jung; Pil Whan Yoon; Joon Seon Song; Jae-Joong Kim (Cardiovascular Toxicology, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

Inoculum effect of methicillin-susceptible Staphylococcus aureus against broad-spectrum beta-lactam antibiotics - Kyoung-Ho Song; Sook-In Jung; Shinwon Lee; Sohee Park; Eu Suk Kim; Kyung-Hwa Park; Wan Beom Park; Pyoeng Gyun Choe; Young Keun Kim; Yee Gyung Kwak; Yeon-Sook Kim; Hee-Chang Jang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Development and preclinical trials of a wire-driven end effector device for frozen shoulder treatment - Chul Min Park; Seong-il Kwon; Hanpyo Hong; Sungchul Kang; In-Ho Jeon; Shinsuk Park; Keri Kim (Medical & Biological Engineering & Computing, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The Korean Integrated Model (KIM) System for Global Weather Forecasting - Song-You Hong; Young Cheol Kwon; Tae-Hun Kim; Jung-Eun Esther Kim; Suk-Jin Choi; In-Hyuk Kwon; Junghan Kim; Eun-Hee Lee; Rae-Seol Park; Dong-Il Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Matrix Metalloproteinase-8 Inhibition Prevents Disruption of Blood–Spinal Cord Barrier and Attenuates Inflammation in Rat Model of Spinal Cord Injury - Hemant Kumar; Min-Jae Jo; Hyemin Choi; Manjunatha S. Muttigi; Seil Shon; Byung-Joo Kim; Soo-Hong Lee; In-Bo Han (Molecular Neurobiology, 2018)

Whitening and anti-wrinkle activities of ferulic acid isolated from Tetragonia tetragonioides in B16F10 melanoma and CCD-986sk fibroblast cells - Hye-Jin Park; Jun-Hyo Cho; Shin-Hyub Hong; Dong-Hee Kim; Hee-Young Jung; In-Kyu Kang; Young-Je Cho (Journal of Natural Medicines, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Effects of vascular formation during alveolar bone process morphogenesis in mice - Seo-Young An; Ye-Ji Lee; Sanjiv Neupane; Jong-Hwa Jun; Ji-Youn Kim; Youngkyun Lee; Karp-Shik Choi; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Wern-Joo Sohn; Jae-Young Kim (Histochemistry and Cell Biology, 2017)

Genetic analysis of a novel reassortant H11N9 Isolated from waterfowl in South Korea in 2016 - Tran Bac Le; In Hong Lee; Hyun Soo Kim; Seung Kyoo Oh; Sang Heui Seo (Virus Genes, 2017)

Recovery of renal function after administration of adipose-tissue-derived stromal vascular fraction in rat model of acute kidney injury induced by ischemia/reperfusion injury - Chunwoo Lee; Myoung Jin Jang; Bo Hyun Kim; Jin Young Park; Dalsan You; In Gab Jeong; Jun Hyuk Hong; Choung-Soo Kim (Cell and Tissue Research, 2017)

The long-term variability of Changma in the East Asian summer monsoon system: A review and revisit - June-Yi Lee; MinHo Kwon; Kyung-Sook Yun; Seung-Ki Min; In-Hong Park; Yoo-Geun Ham; Emilia Kyung Jin; Joo-Hong Kim; Kyong-Hwan Seo; WonMoo Kim; So-Young Yim; Jin-Ho Yoon (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Porcine mast cells infected with H1N1 influenza virus release histamine and inflammatory cytokines and chemokines - In Hong Lee; Hyun Soo Kim; Sang Heui Seo (Archives of Virology, 2017)

Simultaneous estimation of saponin contents from soybean seed using Fourier transform infrared spectroscopy and high-performance liquid chromatography analysis - Myung Suk Ahn; Eun Yee Jie; Seung Yeob Song; Hong Sig Kim; In-Jung Kim; Suk Weon Kim (Plant Biotechnology Reports, 2016)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Reduction of GIGANTEA expression in transgenic Brassica rapa enhances salt tolerance - Jin A. Kim; Ha-eun Jung; Joon Ki Hong; Victor Hermand; C. Robertson McClung; Yeon-Hee Lee; Joo Yeol Kim; Soo In Lee; Mi-Jeong Jeong; Jungsun Kim; DaeJin Yun; WeoYeon Kim (Plant Cell Reports, 2016)

The assessment of droughts in Northern China and Mongolian areas using PDSI and relevant large‐scale environments - Jae‐Won Choi; In‐Gyum Kim; Jeoung‐Yun Kim; Baek‐Jo Kim; Cheol‐Hong Park; Do‐Woo Kim (International Journal of Climatology, 2016)
This study assessed drought conditions in northern China and Mongolian areas using the Palmer drought severity index ( PDSI ). Droughts in this area were intensified throughout all seasons. In particular, this intensifying trend was pronounced in the summer and autumn. In the summer, the PDSI showed an overall increase from the early 1990s to the late 1990s, and then, it rapidly decreased after the late 1990s. Therefore, this study focused on summer droughts and analysed mean differences before the late 1990s (9098) and after the late 1990s (9905). Regarding differences in 850 hPa stream flows between the two periods, anomalous anticyclonic circulations were strengthened in northern China and Mongolia that showed strong negative anomalies in the PDSI . These anomalous anticyclones were formed as a positive North Atlantic Oscillation pattern formed in the European region spread eastward in the form of wave trains. The anomalous anticyclones formed in northern China and Mongolia led to reduced total cloud cover. As a result, this region exhibited high sensible heat net fluxes. Consequently, warm and dry anticyclones may have recently been strengthened in this region, thereby intensifying droughts. As this shows, recently strengthened warm and dry anticyclones in northern China and Mongolia were associated with recently reduced snow depths in this region during the preceding spring. In recent years, the frequency of Asian dust has also increased due to warm and dry air conditions.

LED light for in vitro and ex vitro efficient growth of economically important highbush blueberry (Vaccinium corymbosum L.) - Cao Dinh Hung; Chang-Hee Hong; Seon-Ki Kim; Kyu-Han Lee; Jea-Young Park; Min-Woo Nam; Dae-Ho Choi; Hye-In Lee (Acta Physiologiae Plantarum, 2016)

Phentermine induces conditioned rewarding effects via activation of the PI3K/Akt signaling pathway in the nucleus accumbens - Sa-Ik Hong; Min-Jung Kim; In-Jee You; Seung-Hwan Kwon; Shi-Xun Ma; Ji-Young Hwang; Jee-Yeon Seo; Yong-Hyun Ko; Bo Ram Lee; Seok-Yong Lee; Choon-Gon Jang (Psychopharmacology, 2016)

Extracellular calcium-binding peptide-modified ceramics stimulate regeneration of calvarial bone defects - Ju Ang Kim; Young-Ae Choi; Hui-Suk Yun; Yong Chul Bae; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2016)

Isolation of a novel H3N2 influenza virus containing a gene of H9N2 avian influenza in a dog in South Korea in 2015 - In Hong Lee; Tran Bac Le; Hyun Soo Kim; Sang Heui Seo (Virus Genes, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Inhibition of Mitochondrial Clearance and Cu/Zn-SOD Activity Enhance 6-Hydroxydopamine-Induced Neuronal Apoptosis - Sua In; Chang-Won Hong; Boyoung Choi; Bong-Geum Jang; Min-Ju Kim (Molecular Neurobiology, 2016)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Relationship between cold hardiness and dehydrin gene expression in peach shoot tissues under field conditions - Hyunsuk Shin; Sung-Il Oh; Min-Ah Kim; Seok Kyu Yun; Youngjae Oh; In-Chang Son; Hong-Sig Kim; Daeil Kim (Horticulture, Environment, and Biotechnology, 2015)

Genome-wide analysis of the expansin gene superfamily reveals Brassica rapa-specific evolutionary dynamics upon whole genome triplication - Panneerselvam Krishnamurthy; Joon Ki Hong; Jin A Kim; Mi-Jeong Jeong; Yeon-Hee Lee; Soo In Lee (Molecular Genetics and Genomics, 2015)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

SMOC1-induced osteoblast differentiation involves enhanced proliferation of human bone marrow mesenchymal stem cells - Young-Ae Choi; Dong-Sung Kim; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Cryptotanshinone induces G1 cell cycle arrest and autophagic cell death by activating the AMP-activated protein kinase signal pathway in HepG2 hepatoma - In-Ja Park; Woo Kyeom Yang; Sang-Hee Nam; Jongki Hong; Ki Ryeol Yang; Joungmok Kim; Sung Soo Kim; Wonchae Choe; Insug Kang; Joohun Ha (Apoptosis, 2014)

Escitalopram block of hERG potassium channels - Yun Ju Chae; Ji Hyun Jeon; Hong Joon Lee; In-Beom Kim; Jin-Sung Choi; Ki-Wug Sung; Sang June Hahn (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Phellinus baumii ethyl acetate extract alleviated collagen type II induced arthritis in DBA/1 mice - Taddesse Yayeh; Whi Min Lee; Dukhwan Ko; Seung-Choon Park; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Seung-Hyung Kim; Seung-Bok Hong; Suk Kim; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

Overexpression of a Brassica rapa MADS-box gene, BrAGL20, induces early flowering time phenotypes in Brassica napus - Joon Ki Hong; Soo-Yun Kim; Kwang-Soo Kim; Soo-Jin Kwon; Jung Sun Kim; Jin A. Kim; Soo In Lee; Yeon-Hee Lee (Plant Biotechnology Reports, 2013)

Natural production of alkane by an easily harvested freshwater cyanobacterium, Phormidium autumnale KNUA026 - Jiwon Chang; Ji Won Hong; Hyunsik Chae; Han Soon Kim; Kyung Mok Park; Kyoung In Lee; Ho-Sung Yoon (Algae, 2013)

Prediction of the tacrolimus population pharmacokinetic parameters according to CYP3A5 genotype and clinical factors using NONMEM in adult kidney transplant recipients - Nayoung Han; Hwi-yeol Yun; Jin-yi Hong; In-Wha Kim; Eunhee Ji; Su Hyun Hong; Yon Su Kim; Jongwon Ha; Wan Gyoon Shin; Jung Mi Oh (European Journal of Clinical Pharmacology, 2013)

Synergistic Effect and Antibiofilm Activity Between the Antimicrobial Peptide Coprisin and Conventional Antibiotics Against Opportunistic Bacteria - In-sok Hwang; Jae-Sam Hwang; Ji Hong Hwang; Hyemin Choi; Eunjung Lee; Yangmee Kim; Dong Gun Lee (Current Microbiology, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

A novel COCH mutation associated with autosomal dominant nonsyndromic hearing loss disrupts the structural stability of the vWFA2 domain - Hyun-Ju Cho; Hong-Joon Park; Maria Trexler; Hanka Venselaar; Kyu-Yup Lee; Nahid G. Robertson; Jeong-In Baek; Beom Sik Kang; Cynthia C. Morton; Gert Vriend; László Patthy; Un-Kyung Kim (Journal of Molecular Medicine, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Overexpression of Brassica rapa SHI-RELATED SEQUENCE genes suppresses growth and development in Arabidopsis thaliana - Joon Ki Hong; Jin A. Kim; Jung Sun Kim; Soo In Lee; Bon Sung Koo; Yeon-Hee Lee (Biotechnology Letters, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

A promoter polymorphism of MSTN g.−371T>A and its associations with carcass traits in Korean cattle - Sang-Hyun Han; In-Cheol Cho; Moon-Suck Ko; Eun-Young Kim; Se-Pill Park; Sung-Soo Lee; Hong-Shik Oh (Molecular Biology Reports, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Phellinus baumii ethyl acetate extract inhibits lipopolysaccharide-induced iNOS, COX-2, and proinflammatory cytokine expression in RAW264.7 cells - Taddesse Yayeh; Won Jun Oh; Seung-Choon Park; Tae-Hwan Kim; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Sang-Keun Kim; Seung-Bok Hong; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2012)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Environmental quality of Korean coasts as determined by modified Shannon–Wiener evenness proportion - Jae-Won Yoo; Yong-Woo Lee; Jennifer L. Ruesink; Chang-Gun Lee; Chang-Soo Kim; Mi-Ra Park; Kon-Tak Yoon; In-Seo Hwang; Jun-Ho Maeng; Rutger Rosenberg; Jae-Sang Hong (Environmental Monitoring and Assessment, 2010)

Increase of isoflavones in soybean callus by Agrobacterium-mediated transformation - Nan Jiang; Eun-Hee Jeon; Jung-Hun Pak; Tae-Joung Ha; In-Youl Baek; Woo-Suk Jung; Jai-Heon Lee; Doh-Hoon Kim; Hong-Kyu Choi; Zheng Cui; Young-Soo Chung (Plant Biotechnology Reports, 2010)

Effect of combined indole acetic acid and mepiquat chloride on endogenous gibberellins and tuber growth in Chinese yam (Dioscorea opposita Thunb.) - Sang Kuk Kim; Hong Jib Choi; In Jung Lee; Hak Yoon Kim (Journal of Crop Science and Biotechnology, 2010)

Reexamination of the genus Pterocladiella (Gelidiaceae, Rhodophyta) in Korea based on morphology and rbcL sequences - Sung-Min Boo; Su-Yeon Kim; In-Sun Hong; Il-Ki Hwang (Algae, 2010)

Ailanthus altissima swingle has anti-anaphylactic effect and inhibits inflammatory cytokine expression via suppression of nuclear factor-kappaB activation - Tae-Hee Kang; In-Young Choi; Su-Jin Kim; Phil-Dong Moon; Jae-Uk Seo; Jae-Joong Kim; Nyeon-Hyung An; Sung-Hoon Kim; Min-Ho Kim; Jae-Young Um; Seung-Heon Hong; Hyung-Min Kim; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Electricity generation coupled to oxidation of propionate in a microbial fuel cell - Jae Kyung Jang; In Seop Chang; Hwa Yeon Hwang; Yeng Fung Choo; JiYoung Lee; Kyung Suk Cho; Byung Hong Kim; Kenneth H. Nealson (Biotechnology Letters, 2010)

Breeding of four-leaf white clover (Trifolium repens L.) through 60Co gamma-ray irradiation - In-Ja Song; Hong-Gyu Kang; Ji-Yeon Kang; Hae-Deun Kim; Tae-Woong Bae; Si-Young Kang; Pyung-Ok Lim; Taiji Adachi; Hyo-Yeon Lee (Plant Biotechnology Reports, 2009)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Clostridium difficile toxin A promotes dendritic cell maturation and chemokine CXCL2 expression through p38, IKK, and the NF-κB signaling pathway - Jin Young Lee; Hyunah Kim; Mi Yeon Cha; Hong Gyu Park; Young-Jeon Kim; In Young Kim; Jung Mogg Kim (Journal of Molecular Medicine, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

AGHR polymorphism and its associations with carcass traits in Harrwoo cattle - Sang-Hyun Han; In-Cheol Cho; Jin-Hyoung Kim; Moon-Suck Ko; Ha-Yeon Jeong; Hong-Shik Oh; Sung-Soo Lee (Genes & Genomics, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Induced metabolite changes inMyriophyllum spicatum during co-existence experiment with the cyanobacteriumMicrocystis aeruginosa - Sungjin Nam; Sungbae Joo; Sunghwan Kim; Nam -In Baek; Hong -Keun Choi; Sangkyu Park (Journal of Plant Biology, 2008)

Effects of lead on bioaccumulation patterns and the ecophysiological response inMonochoria korsakowi - In Sung Kim; Young Hwa Hong; Kyung Hong Kang; Eun Ju Lee (Journal of Plant Biology, 2008)

Perfluorooctanoic acid-induced hepatic toxicity following 21-day oral exposure in mice - Hee-Young Son; Sang-Hyun Kim; Hong-In Shin; Han Ik Bae; Jae-Ho Yang (Archives of Toxicology, 2008)

Function of a novel GDSL-type pepper lipase gene, CaGLIP1, in disease susceptibility and abiotic stress tolerance - Jeum Kyu Hong; Hyong Woo Choi; In Sun Hwang; Dae Sung Kim; Nak Hyun Kim; Du Seok Choi; Young Jin Kim; Byung Kook Hwang (Planta, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Acute hypoxia induces vasodilation and increases coronary blood flow by activating inward rectifier K+ channels - Won Sun Park; Youn Kyoung Son; Nari Kim; Jae-Hong Ko; Sung Hyun Kang; Mohamad Warda; Yung E. Earm; In Duk Jung; Yeong-Min Park; Jin Han (Pflügers Archiv - European Journal of Physiology, 2007)

Use of an industrial grade medium and medium enhancing effects on high cell density CO fermentation by Eubacterium limosum KIST612 - In Seop Chang; Daehee Kim; Byung Hong Kim; Robert W. Lovitt (Biotechnology Letters, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

Recombinant expression of human cathelicidin (hCAP18/LL-37) in Pichia pastoris - In-Pyo Hong; Sung-Jae Lee; Yong-Seok Kim; Shin-Geon Choi (Biotechnology Letters, 2006)

Characterization of copper, zinc superoxide dismutase from a cartilaginous shark species, Scyliorhinus torazame (Carcharhiniformes) - Yoon Kwon Nam; Young Sun Cho; Keun-Yong Kim; In Chul Bang; Ki Hong Kim; Sung Koo Kim; Dong Soo Kim (Fish Physiology and Biochemistry, 2006)

UV Spectroscopic Monitoring of Vaporized Monoaromatic Hydrocarbons from Petroleum-Contaminated Soils - Woo Jin Kim; Joo In Lee; Seockhun Lee; Kyu-Hong Ahn; Jae-Woo Park (Environmental Monitoring and Assessment, 2006)

Gamma radiation and hormone treatment as tools to reduce salt stress in rice (Oryza sativa L.) - Myung-Hwa Baek; Byung Yeoup Chung; Jin-Hong Kim; Seung Gon Wi; Jae-Sung Kim; In-Jung Lee (Journal of Plant Biology, 2006)

Optimization of feed conditions in a 2.5-l fed-batch culture using rice oil to improve cephalosporin C production by Cephalosporium acremonium M25 - Na Ri Kim; Jung Soo Lim; Suk In Hong; Seung Wook Kim (World Journal of Microbiology and Biotechnology, 2005)

Expression of recombinant endostatin in Agrobacterium-inoculated leaf-disks of Nicotiana tabacum var. xanthi - Seong Hyun Hong; Kyung Il Kim; Ho Yong Chung; You Jung Kim; Garry Sunter; David M. Bisaro; In Sik Chung (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

p53 and cell-cycle-regulated protein expression in small intestinal cells after fast-neutron irradiation in mice - Young-Heun Jee; Won-Il Jeong; Tae-Hwan Kim; In-Sun Hwang; Mee-Jung Ahn; Hong-Gu Joo; Su-Hyung Hong; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2005)

Improving the dynamic response of a mediator-less microbial fuel cell as a biochemical oxygen demand (BOD) sensor - Hyunsoo Moon; In Seop Chang; Kui Hyun Kang; Jae Kyung Jang; Byung Hong Kim (Biotechnology Letters, 2004)

Biodegradation of Dibenzo-p-dioxin, Dibenzofuran, and Chlorodibenzo-p-dioxins by Pseudomonas veronii PH-03 - Hyo-Bong Hong; In-Hyun Nam; Kumarasamy Murugesan; Young-Mo Kim; Yoon-Seok Chang (Biodegradation, 2004)

Expression of recombinant endostatin in Agrobacterium-inoculated leaf disks of Nicotiana tabacum var. Xanthi - Seong Hyun Hong; Kyung Il Kim; Ho Yong Chung; You Jung Kim; Garry Sunter; David M. Bisaro; In Sik Chung (Biotechnology Letters, 2004)

Micropropagation ofSchizandra chinensis BAILLON using glucose from cotyledonary nodes - Min Hee Hong; Ok Tae Kim; Jae In Park; Baik Hwang (Journal of Plant Biology, 2004)

Novel Leuconostoc citreum starter culture system for the fermentation of kimchi, a fermented cabbage product - In-Kwon Choi; Seok-Ho Jung; Bong-Joon Kim; Sae-Young Park; Jeongho Kim; Hong-Ui Han (Antonie van Leeuwenhoek, 2003)

A microbial fuel cell with improved cathode reaction as a low biochemical oxygen demand sensor - Kui Hyun Kang; Jae Kyung Jang; The Hai Pham; Hyunsoo Moon; In Seop Chang; Byung Hong Kim (Biotechnology Letters, 2003)

Novel BOD (biological oxygen demand) sensor using mediator-less microbial fuel cell - Byung Hong Kim; In Seop Chang; Geun Cheol Gil; Hyung Soo Park; Hyung Joo Kim (Biotechnology Letters, 2003)

Fed-batch cultivation for the production of clavulanic acid by an immobilized Streptomyces clavuligerus mutant - Il-Chul Kim; Chang-Ho Kim; Suk-In Hong; Seung-Wook Kim (World Journal of Microbiology and Biotechnology, 2001)

A novel bioreactor with an internal adsorbent for integrated fermentation and recovery of prodigiosin-like pigment produced from Serratia sp. KH-95 - Jungdon Bae; Hyunsoo Moon; Kyeong-Keun Oh; Chang-Ho Kim; Dae Sil Lee; Seung-Wook Kim; Suk-In Hong (Biotechnology Letters, 2001)

Improved production of recombinant rotavirus VP6 in sodium butyrate-supplemented suspension cultures of transgenic tomato (Lycopersicon esculentum Mill.) cells - Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Youn Hyung Lee; In Sik Chung (Biotechnology Letters, 2001)

Purification and biochemical characterization of a fibrinolytic enzyme from Bacillus subtilis BK-17 - Yong Kee Jeong; Jeong Uck Park; Hyun Baek; Sung Hoon Park; In Soo Kong; Dong Wan Kim; Woo Hong Joo (World Journal of Microbiology and Biotechnology, 2001)

Intermittent maltose feeding enhances paclitaxel production in suspension culture of Taxus chinensis cells - Hyung-Kyoon Choi; Sang-Ic Kim; Joo-Sun Son; Seung-Suh Hong; Hyun-Soo Lee; In-Sik Chung; Hyong-Joo Lee (Biotechnology Letters, 2000)

Fractional precipitation for paclitaxel pre-purification from plant cell cultures of Taxus chinensis - Jin-Hyun Kim; In-Seon Kang; Hyung-Kyoon Choi; Seung-Suh Hong; Hyun-Soo Lee (Biotechnology Letters, 2000)

Karyotypes of three somaclonal variants and wild plants ofAllium tuberosum by bicolor FISH - Geum-Sook Do; Bong-Bo Seo; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Journal of Plant Biology, 2000)

Production of recombinant rotavirus VP6 from a suspension culture of transgenic tomato (Lycopersicon esculentum Mill.) cells - In Sik Chung; Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Jong Hwa Park; Ju Kon Kim; Won Yong Kim (Biotechnology Letters, 2000)

Ultrastructure of leaves in C4 Cyperus iria and C3 Carex siderosticta - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1999)

Analysis of somaclonal variation through tissue culture and chromosomal localization of rDNA sites by fluorescent in situ hybridization in wild Allium tuberosum and a regenerated variant - Geum-Sook Do; Bong-Bo Seo; Jong-Min Ko; Seon-Hee Lee; Jae-Hong Pak; In-Sun Kim; Seung-Dal Song (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Ultrastructural aspects of leaves inFestuca ovina andPoa sphondylodes (C-3 Poaceae) - In Sun Kim; Jae-Hong Pak; Bong-Bo Seo; Seung-Dal Song (Journal of Plant Biology, 1998)